Rosette-forming glioneuronal tumor of the fourth ventricle - Da-chun ZHAO; Wen-bin MA; Jun GAO; Tao LU; Ding-rong ZHONG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2015)
Objective To explore the clinicopathological features of rosette-forming glioneuronal tumor (RGNT) of the fourth ventricle.  Methods The clinical manifestations, neuroimaging, histopathological and immunohistochemical features were analysed in one case of RGNT of the fourth ventricle, and related literatures were reviewed.  Results A 24-year-old female presented with progressive dizziness under no obvious predisposing causes and dyskinesia such as stumbling. MRI revealed expansion of the fourth ventricle, and a mass with long T1WI and T2WI signal and clear boundary could be seen within the fourth ventricle. The border of tumor showed slight enhancement. At surgery, it was observed that the solitary tumor arised from the fourth ventricle and appeared well demarcated with rhomboid fossa. The tumor was blocking the aqueduct of sylvius before it was removed. Microscopically, the tumor exhibited both neuronic and astrocytic components. In the neuronic components, neurocytes formed neurocytic rosettes and perivascular pseudorosettes. At the center of the neurocytic rosettes, there was an eosinophilic core and some region consisted of microcysts. While the astrocytic components of the tumor revealed typical pilocytic astrocytoma structure. The center of neuronic rosettes and perivascular pseudorosettes displayed strong positive staining with synaptophysin (Syn) and oligodendrocytes transcription factor-2 (Olig-2). The astrocytic components showed positive immunostaining of glial fibrillary acidic protein (GFAP). There were focal and partial positive immunostaining of neuron-specific enolase (NSE) in both components of the tumor. The Ki-67 labeling index was 1.50%-2.00% in two components.  Conclusions Rosette-forming glioneuronal tumor of the fourth ventricle is an unusual neuronal and mixed neuronal-glial tumors. The imaging examination showed solid or mixed solid-cystic mass at the fourth ventricle with well demarcated border. The lesion has two characteristic components and the distinctive immunostaining of GFAP and Syn expression will help the differential diagnosis.   DOI: 10.3969/j.issn.1672-6731.2015.11.013